Young population in the distric of Bragança: concerning demographic indicators - Pimentel, Maria Helena (2013)
Portugal has a very high aging rate (19%). The number of the elderly is of 39 thousand, of which around 24 000 (63% of the total) live alone or with other elderly (INE; 2011). The proportion of old people living in the district of Bragança increases to 29%. This district lengths 6608 Km2 and has a population of 136,252, corresponding to a population density of 21 inhabitants per km2. To analyse this region’s demographic indicators, according to the young population versus old population, is the aim of the present study.